(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2013)
يشكل القطاع المصرفي عصباً رئيسيِّاً في اقتصاد أي دولة نظراً للخدمات الكبيرة التي يوفرها للحياة الاقتصاديِّة في أي مجتمع, فضلاً عن الدور التنموي الكبير الذي يقوم به بصفته محركاً ودافعاً لعجلة التنمية. وكباقي المؤسسات الأخرى تبدو المصارف خاضعة لعنصر المنافسة فيما بينها في مجال منح الائتمان. رافق التطورات الكبيرة التي شهدها القطاع المالي على مستوى العالم والتي تمثلت في التقدم التكنولوجي الهائل في الصناعة المصرفيِّة، واستحداث أدوات ماليِّة جديدة بعض الأزمات المالية، ومعظم الأزمات التي شهدها القطاع المالي كانت مشاكل البنوك قاسماً مشتركاً فيها، وأرجع الخبراء ذلك إلى تزايد المخاطر المصرفيِّة وعلى رأسها المخاطر الناتجة عن الائتمان, ولذلك كان لابد لكل مصرف من وضع ضوابط محددة تضمن له إمكانية التوسع في منح الائتمان مع الحفاظ على المخاطرة ضمن الحدود المقبولة, وهذا ما يتطلب توفر نظام كفوء للتحليل الائتماني. ومن هنا فقد سعى الباحث من خلال هذا البحث إلى التركيز على الدراسة الائتمانية التي تجرى في المصرف التجاري السوري والتي تغفل الكثير من الجوانب الهامة التي يتوجب دراستها والتي قد تشكل منطلقاً للخطر الذي يقود بدوره إلى التعثر مستقبلاً, حيث اعتمد الباحث في القسم النظري على المنهج الوصفي لأهم ما ورد في الكتب والمرجعيات المالية والمصرفية, كما تم الاعتماد على الدراسة الميدانية في الجانب العملي للتعرف على واقع الدراسات التي يجريها المصرف التجاري السوري قبل منح القروض والتسهيلات. وهدف الباحث من خلال هذه الدراسة إلى التحقق من وجود نظام معتمد للتحليل الائتماني لدى المصرف التجاري السوري, ومدى كفاءة التحليل الائتماني في المصرف التجاري للحد من حجم المخاطر الائتمانية المرتبطة بمنح القروض. ومن أهم نتائج البحث عدم شمولية نظام النظام التحليل الائتماني لدى المصرف التجاري السوري ولاسيما ما يتعلق بالنسب المالية المستخدمة في عملية التحليل, واعتماد منهج التنويع للتخفيف من المخاطر المرتبطة بمنح الائتمان, وتركيز المصرف على الضمانات العينية والشخصية من أجل منح القروض, ويغفل التحليل الائتماني التعرف على الغاية من منح القرض وكذلك تاريخ التعاملات المصرفية لطالب الائتمان مع المصارف الأخرى. The banking sector shapes a main backbone of economy in any country, given the great services provided by the economic life in any society, in addition to the significant developmental role play as a motivator and a engine of development wheel, and like all other institutions banks seem subject to the competition element among them in the domain of credit granting. The significant developments in the financial sector at the level of the world marked by the enormous technological progress in the banking industry, and the introduction of new financial instruments some financial crises, and most of the crises in the financial sector problems were common denominator where the banks, experts attributed this to increased risks, led by banking credit risk arising from credit granting, therefore it was necessary for each bank to put specific controls that guarantee the possibility of increasing granting credit while maintaining risk within acceptable limits, this requires the availability of an efficient system of credit analysis. Here they sought researcher of this study is to focus on the study of credit made ​​in the Commercial Bank of Syria, which overlook a lot of the important aspects that need to be studied and which may constitute a starting point for risk, Which leads in turn to stumble in the future, the researcher in theoretical section depended on the descriptive approach to what is stated in the most important books and references Banking and Finance, and depended on field study in the practical side to get to know the reality of the studies conducted by the Commercial Bank of Syria before granting loans and advances. The goal of the researcher of this study to verify the existence of a certified system of credit analysis at the Commercial Bank of Syria, and the efficiency analysis in commercial bank credit to reduce the size of the credit risk associated with the granting of loans. The most important results lack a holistic system of system credit analysis at the Commercial Bank of Syria, particularly with regard to financial ratios used in the analysis process, the adoption of curriculum diversification to reduce risks associated with the granting of credit, The bank’s focus on collateral and personal for the granting of loans, and credit analysis neglects to identify the purpose of the granting of the loan as well as the history of banking transactions for credit applicants with other banks.